2019
DOI: 10.1111/aje.12621
|View full text |Cite
|
Sign up to set email alerts
|

Impact of environmental conditions on fruit production patterns of shea tree (Vitellaria paradoxa C.F.Gaertn) in West Africa

Abstract: A better knowledge of the impact of environmental conditions on shea tree’s fruit production is critical to improve the species management. Fruit production of 237 shea trees was monitored over five successive years (2014–2018) to understand how climatic variables, shea tree population and land use could affect fruit production patterns of the species in Burkina Faso. Data were collected in 12 shea tree populations distributed in three climatic zones with two contrast land use systems. The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 42 publications
(53 reference statements)
0
15
0
Order By: Relevance
“…Oyerinde et al (2018) reported a possible effect of land use type on the difference between sites with respect to P. biglobosa fruit variables. For V. paradoxa (another parkland tree species), several authors have reported that human activities have a positive influence on fruit production and this positive effect is partly due to agricultural practices like reduction of tree density, plowing, weeding and crops fertilization, tree selection (Lamien et al, 2004;Okullo et al, 2004;Kelly et al, 2007;Bondé et al, 2013;Kelly et al, 2019). A significant effect of land use on fruit production has also been reported for Sclerocaya birrea (Shackleton et al, 2002) and for Lannea microcarpa (Haameyer et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Oyerinde et al (2018) reported a possible effect of land use type on the difference between sites with respect to P. biglobosa fruit variables. For V. paradoxa (another parkland tree species), several authors have reported that human activities have a positive influence on fruit production and this positive effect is partly due to agricultural practices like reduction of tree density, plowing, weeding and crops fertilization, tree selection (Lamien et al, 2004;Okullo et al, 2004;Kelly et al, 2007;Bondé et al, 2013;Kelly et al, 2019). A significant effect of land use on fruit production has also been reported for Sclerocaya birrea (Shackleton et al, 2002) and for Lannea microcarpa (Haameyer et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Fan et al compared the changes of geographical distribution of Rosa roxburghii in China in current, 2050s and 2070s under RCP4.5 and RCP8.5 scenarios based on MaxEnt [57]. There are many environmental factors affecting the growth and distribution of fruit trees, such as climate, soil type, vegetation type, topographic factor, variety type, biotic interactions and human activities [58][59][60]. In addition to climate variables, the future changes of most other variables cannot be evaluated quantitatively at present.…”
Section: Terrain Suitability Analysismentioning
confidence: 99%
“…Both women and men have commercialized the shea tree [181,182]. The commercialization of shea tree kernels contributes 66% to household income in Burkina Faso [178].…”
Section: The Role Of V Paradoxa In Food Security and Socio-economic D...mentioning
confidence: 99%